2022
DOI: 10.21203/rs.3.rs-1633422/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic regulation of human brain proteome reveals proteins implicated in psychiatric disorders

Abstract: Psychiatric disorders are highly heritable yet polygenetic, potentially involving hundreds of risk genes. Genome-wide association studies (GWAS) have identified hundreds of genomic susceptibility loci for psychiatric disorders, but how these loci contribute to the underlying psychopathology and etiology remains elusive. Here we generated a deep human brain proteome by quantifying 11,672 proteins across 288 subjects using 11-plex tandem mass tag (TMT) coupled with two-dimensional liquid chromatography-tandem ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The quantified proteins cover ∼70% of the range of transcripts detected by the transcriptomic data ( Figure S3A ). A moderate positive correlation between expression levels of mRNAs and proteins ( r = 0.35) was observed ( Figure S3B ), which is consistent with previous findings in human study 24 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The quantified proteins cover ∼70% of the range of transcripts detected by the transcriptomic data ( Figure S3A ). A moderate positive correlation between expression levels of mRNAs and proteins ( r = 0.35) was observed ( Figure S3B ), which is consistent with previous findings in human study 24 .…”
Section: Resultssupporting
confidence: 92%
“…To investigate the genetic basis of trait variation in molecular endophenotypes, genetic reference populations, such as the mouse BXDs 1719 , Collaborative Cross 20,21 , and the HXB/BXH recombinant inbred (RI) family 22,23 , have been used extensively over the past decade, but surprisingly never to study protein levels in the brain in any species other than humans 24 . The HXB/BXH family is the largest and most deeply phenotyped set of genetically diverse but fully inbred set of rats.…”
Section: Introductionmentioning
confidence: 99%
“…blood plasma sample storage time or co-ordinates on measurement plate). Technical artifacts, such as batch effects and some confounding factors can be accounted for to improve power and decrease the risk of false associations 53, 54 . For each aptamer, we performed multiple regression with the following covariates: biological sex, age, sample storage time in the freezer, season of the year when the plasma sample was taken, 96-well measurement plate number, row, and column.…”
Section: Methodsmentioning
confidence: 99%
“…an eQTL) has been shown to be prevalent ( 19 ). In addition, QTLs specific to protein level have also been reported ( 19-21 ). Together, these observations indicated the importance and potential benefits of including downstream omics types, such as proteomics data, as information sources for fine mapping disease regulatory variants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies using multi-omics approaches have demonstrated increased power for risk gene identification among other benefits ( 22 , 23 ). Of note, our recent work on genetic variants associated with protein level in prefrontal cortex of the human brain indicated the extent of contribution from non-synonymous coding variants to changes at the protein level, and the utility of these protein QTL variants in prioritizing GWAS risk genes for psychiatric disorders ( 21 ).…”
Section: Introductionmentioning
confidence: 99%